GPR and ERT detection and characterization of a mass burial, Spanish Civil War, Northern Spain. (June 2018) - Rubio-Melendi, David; Gonzalez-Quirós, Andrés; Roberts, Daniel; García García, María del Carmen; Caunedo Domínguez, Amaya; Pringle, Jamie K.; Fernández-Álvarez, José-Paulino
Highlights: We detail a study of the cemetery of Oviedo (Spain), which contains a mass burial. GPR and ERT were used to enhance knowledge about their response to mass graves. The results have established the limits of the grave and the internal structure. We also show the importance of considering the climatology during data acquisition. Abstract: Around 27, 000 people were killed in the province of Asturias during the Spanish Civil War, with several thousands killed after the war ended. There are currently over 2, 000 known mass burial locations throughout Spain, but many more are unknown. Geophysics is a useful tool employed to help in the active attempts to document and improve knowledge about victims from this conflict. This paper details a non-invasive study of the Cementerio de El Salvador, in the city of Oviedo, Northern Spain. Part of the cemetery contains a known mass burial with approximately 1, 300 individuals from the Spanish Civil War and post-war repression eras. Multi-frequency near-surface geophysical techniques were undertaken, after permission, to enhance knowledge about which, if any, techniques should be used to detect, delineate and analyse such mass graves. Multi-frequency (250 MHz and 500 MHz) ground-penetrating radar surveys were acquired together with 2D and 3D Electrical Resistivity Tomography datasets. The results have established the limits of the mass grave and improve the knowledge of the internal mass grave structure. The paper also shows the importance of considering the climatic conditions during data acquisition. This has important implications for the successful detection of recent historical mass burials using near-surface geophysics.